"Krajoznawstwo” in relation to different forms of active and cognitive tourism - Poczta, Joanna; Rozmiarek, Mateusz (Journal of Education, Health and Sport, 2021)
The main goal of the manuscript is an attempt to show that contemporary trends in tourism are based on forms in which cognitive, adventure and educational tourism is becoming more and more important. All these forms are based on the natural, cultural and historical heritage of the regions. In Poland, “krajoznawstwo” is an important trend, which for years has been based on the educational, cognitive and active tourism functions. It turns out that it is very difficult to find an equivalent of this word in English, but the message "get to know your country" can be carried out anywhere, in any part of the world. We decided to use the word "touring" in the text.